Head and neck Ewing sarcoma: French surgical practice analysis pleads for surgery centralization. Issue 5 (May 2022) - Bouaoud, Jebrane; Temam, Stephane; Galmiche, Louise; Cozic, Nathalie; Bolle, Stephanie; Belhous, Kahina; Kolb, Frederic; Qassemyar, Quentin; Bidault, Francois; Couloigner, Vincent; Picard, Arnaud; Le Deley, Marie-Cécile; et al.
Abstract: This study aimed to analyze surgical procedures for head and neck Ewing sarcoma (HNES) with regard to oncological, functional, and esthetic outcomes. A blinded multidisciplinary retrospective chart review of operated French HNES patients (Euro-EWING 99 trial, 1999–2014) was performed to assess patient/tumor characteristics, treatment details, and outcomes. Primary surgery without reconstruction was undertaken in 13 patients (emergency context/misdiagnosis). However, because of contaminated surgical margins, all patients had to undergo systematic postoperative radiotherapy. Twenty-six patients underwent multidisciplinary evaluation and were scheduled to undergo postchemotherapy surgery, with 19 patients scheduled for immediate reconstruction. All cases showed R0 margins after postchemotherapy surgery of the initial tumor bed by multidisciplinary surgical teams, while n = 3/4 of local relapses (very poor prognosis) had R1a margins after surgery of the residual tumor volume following chemotherapy. Only three surgical expertise centers operated on ≥ 4 patients over the 15-year period. Thirty patients developed long-term sequelae, with increased complications following radiotherapy. Referring patients to surgical expertise centers following a suspected diagnosis, with planned postchemotherapy surgery of the initial tumor bed at these centers, might limit the need for intralesional resections, allowing radical R0 resections and thus reducing long-term sequelae as well as the risk of secondary radio-induced malignancy by limiting the need for postoperative radiotherapy.